Miss julia weathers the storm eaudiobook Miss julia series, book 19. - Ross, Ann B. (Miss Julia, 2017)
In the latest installment of Ann B. Ross's New York Times bestselling series, Miss Julia takes a trip to the beach, only to confront a hurricane roiling off the coast-and all the trouble it washes ashore Sweet and generous Sam has decided to take a big group trip to the beach, inviting family and friends including little Latisha, leaving Lillian to enjoy a quiet vacation taking care of only herself. While Miss Julia prepares for the big trip, her longtime friend LuAnne comes to her with a horrifying discovery-her husband Leonard may be cheating on her. When the two discover more convincing evidence, Julia invites LuAnne along to the beach to get away and clear her head-and to keep from doing anything rash. Everyone settles into the rental house and six-year-old Latisha is having a blast searching for seashells when she discovers some much more valuable treasures that have washed up from a strong storm off the coast. As the storm nears, the crew packs up to head back to Abbotsville, and it appears that the strange couple they met on the beach are in a car right behind them-a coincidence, Miss Julia thinks, until they show up in Abbotsville threatening Latisha and demanding that she hand over her newfound treasures. In another highly entertaining and delightful installment in the series by Ann B. Ross, Miss Julia must rely on her quick wit and strong will to protect Latisha, get to the bottom of LuAnne's predicament, and once again save the day.